Improving Critical Thinking Skills Using The Probing Prompting Model In Thematic Learning Of Primary School Students - Annisa Auliyah; Mufarizuddin Mufarizuddin; Fadhilaturrahmi Fadhilaturrahmi; M. Syahrul Rizal; Rusdial Marta (Universitas Muhammadiyah Enrekang, 2023)
This research is based on problems that exist in schools, namely the low level of critical thinking skills among students in elementary schools. This research aims to improve critical thinking skills by using the probing prompting model in thematic learning for Class V Elementary School students. This type of research is classroom action research (PTK). This research was carried out using the probing prompting model. The subjects of this research were class V students at SDN 014 Ganting Damai, totaling 29 students and was carried out from May to June 2023. Classroom action research procedures were carried out through 4 main steps, namely, planning, implementation, observation and reflection. The data collection techniques used are observation sheets, tests, documentation. The research instruments used were syllabus, lesson plans, student observation sheets, and test questions. Analysis of the data used in this research is individual learning completeness and classical completeness. Based on the results of the data that has been obtained, it is clear that all indicators of students' critical thinking abilities have increased from cycle I to cycle II using the probing prompting model. It can be seen that in cycle I the average score was 68.96% and in cycle II the average score was obtained. -an average of 88.35%, in cycle II this was categorized as critical. The amount of increase in each indicator varies. Indicators of critical thinking ability to organize thoughts and express them clearly, logically or make sense have increased very well. Keywords: Critical Thinking Skills, Probing Prompting Model, Thematic Learning